Intellectual Property Rights in China - Devonshire-Ellis, Chris; Scott, Andy.; Woollard, Sam.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This Guide is a detailed overview of all aspects of IPR and protection in China. Produced in association with AWS, the Austrian Federal Bank$1 (Bs specialist IPR unit based in Shanghai, this is an essential work for any businessman trading with or conducting business in China. From covering protocol for dealing with Trade Fairs, to the application processes for trademarks, patents, copyright and licensing, as well as dealing with infringements and enforcement,this guide is a practical reference for any businessman with concerned with their IPR in China.s
Importance of IPR in China -- Historical Development -- Recent Trends in China$1 (Bs IPR Policy -- IPR Laws in China -- Basic Requirements for IPR Registration -- Patent Registration -- Trademark Registration -- Copyright Registration -- Licensing -- Preparing for Trade Fairs -- IPR Protection -- IPR Enforcement in China -- Civil and Criminal IPR Laws.s
Keywords: Economics; Commercial law; Industrial management; Economics/Management Science; Management/Business for Professionals; Law and Economics